Effects of vitamin D supplementation on markers for cardiovascular disease and type 2 diabetes: an individual participant data meta-analysis of randomized controlled trials - Swart, Karin Ma; Lips, Paul; Brouwer, Ingeborg A; Jorde, Rolf; Heymans, Martijn W; Grimnes, Guri; Grübler, Martin R; Gaksch, Martin; Tomaschitz, Andreas; Pilz, Stefan; Eiriksdottir, Gudny; Gudnason, Vilmundur; et al. (The American journal of clinical nutrition, 2018)
Evidence from randomized controlled trials (RCTs) for the causal role of vitamin D on noncommunicable disease outcomes is inconclusive. The aim of this study was to investigate whether there are beneficial or harmful effects of cholecalciferol (vitamin D3) supplementation according to subgroups of remeasured serum 25-hydroxyvitamin D [25(OH)D] on cardiovascular and glucometabolic surrogate markers with the use of individual participant data (IPD) meta-analysis of RCTs. Twelve RCTs (16 wk to 1 y of follow-up) were included. For standardization, 25(OH)D concentrations for all participants (n = 2994) at baseline and postintervention were re-measured in bio-banked serum samples with the use of a certified liquid chromatography-tandem mass spectrometry method traceable to a reference measurement procedure. IPD meta-analyses were performed according to subgroups of remeasured 25(OH)D. Main outcomes were blood pressure and glycated hemoglobin (HbA1c). Secondary outcomes were LDL, HDL, and total cholesterol and triglycerides; parathyroid hormone (PTH); fasting glucose, insulin, and C-peptide; and 2-h glucose. In secondary analyses, other potential effect modifiers were studied. Remeasurement of 25(OH)D resulted in a lower mean 25(OH)D concentration in 10 of 12 RCTs. Vitamin D supplementation had no effect on the main outcomes of blood pressure and HbA1c. Supplementation resulted in 10-20% lower PTH concentrations, irrespective of the 25(OH)D subgroups. The subgroup analyses according to achieved 25(OH)D concentrations showed a significant decrease in LDL-cholesterol concentrations after vitamin D supplementation in 25(OH)D subgroups with <75, <100, and <125 nmol of -0.10 mmol/L (95% CI: -0.20, -0.00 mmol/L), -0.10 mmol/L (95% CI: -0.18, -0.02 mmol/L), and -0.07 mmol/L (95% CI: -0.14, -0.00 mmol/L), respectively. Patient features that modified the treatment effect could not be identified. For the main outcomes of blood pressure and HbA1c, the data support no benefit for vitamin D supplementation. For the secondary outcomes, in addition to its effect on PTH, we observed indications for a beneficial effect of vitamin D supplementation only on LDL cholesterol, which warrants further investigation. This trial was registered at www.clinicaltrials.gov as NCT02551835.